Post-encephalitic epilepsy in patients with acute encephalopathy with biphasic seizures and late reduced diffusion - Nagai, Kota; Kawano, Go; Sakaguchi, Hirotaka; Yokochi, Takaoki; Eshima, Nobuoki; Matsuishi, Toyojiro (Frontiers in Neurology, 2025)
IntroductionAcute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is a prevalent form of acute infection-triggered encephalopathy in children, excluding the unclassified type. It is marked by febrile seizures, referred to as early seizures and subsequent late seizures, along with a reduction in the apparent diffusion coefficient in cortical or subcortical white matter. AESD frequently results in neurological sequelae, including post-encephalitic epilepsy (PEE).MethodsThis retrospective study examined the incidence of PEE and investigated whether therapeutic hypothermia reduced the risk of PEE in 45 patients with AESD treated at St Mary’s Hospital between July 2008 and April 2024. Patients whose Glasgow Coma Scale score was >8 and who had mild clinical symptoms, as judged by the attending physician, between July 2008 and December 2020, did not undergo therapeutic hypothermia. However, all patients with AESD underwent therapeutic hypothermia during the period between January 2021 and April 2024. There were 11, 24, and 10 patients in the Early-Hypo, Late-Hypo, and Non-Hypo groups, respectively.ResultsThe prevalence of PEE among patients with AESD was 26.7% (12 out of 45 patients), with a median observation period of 75 months (IQR 37–98 months, range 20–182 months). Univariate analysis revealed statistically significant differences between patients with and without PEE in several factors, including Glasgow Coma Scale scores between 12 and 24 h after early seizures, and the number of patients with AESD with biphasic course, Tada scores, and the Pediatric Cerebral Performance Category at 6 months post-onset. Multivariate logistic regression analysis identified higher Tada scores as an independent risk factor for developing PEE, and the treatment options of Early-Hypo or Late-Hypo significantly reduced the risk of PEE.ConclusionWhile further prospective studies with larger cohorts are warranted, this study highlights the association between higher Tada scores and an increased risk of PEE in patients with AESD, and the treatment options of Early-Hypo or Late-Hypo significantly reduced the risk of PEE.